Post-socialism is not dead (re)reading the global in comparative education - Silova, Iveta (Bingley, U.K. : Emerald, 2010)
This volume will provide a comparative account of the meanings and processes of post-socialist transformations in education by exploring recent theories, concepts, and debates on post-socialism and globalization in national, regional, and international contexts.
Rediscovering post-socialism in comparative education / Iveta Silova -- Education after the fall of the Berlin Wall : the end of history or the beginning of histories? / Olga Bain -- Policy why(s) : policy rationalities and the changing logic of educational reform in postcommunist Ukraine / Olena Fimyar -- Visions of reform in post-socialist Romania : decentralizsation (through hybridization) and teacher autonomy / Monica E. Mincu, Irina Horga -- Rethinking transition through ideas of 'community' in Hungarian kindergarten curriculum / Zsuzsa Millei, Robert J. Imre -- A framework for understanding dramatic change : educational transformation in post-soviet Russia / Eleoussa Polyzoi, Eduard Dneprov -- The semblance of progress amidst the absence of change : educating for an imagined Europe in Moldova and Albania / Meg P. Gardinier, Elizabeth Anderson Worden -- Rewriting the nation : World War II narratives in Polish history textbooks / Magdalena Gross -- When intolerance means more than prejudice : challengs to Lithuanian education reforms for social tolerance / Christine Beresniova -- Transnational vitality of the Finno-Ugric identity in Estonia : the role of education and advocacy in a new geopolitical context / Kara D. Brown -- The reconfiguration of state-university-student relationships in post/socialist China / Heidi Ross, Ran Zhang, Wanxia Zhao -- Socialist, post-socialist, and post-post socialist transformations of education in Nicaragua / Anita Sanyal -- Staying the (post)socialist course : global/local transformations and Cuban education / Noah W. Sobe, Renee N. Timberlake -- African socialism, post-colonial development, and education : change and continuity in the post-socialist era / Diane Brook Napier -- Beyond post-socialist conversions : functional cooperation and trans-regional regimes in the global south / Tavis D. Jules.
Keywords: Education -- Research; Education -- Guidance & Orientation; Philosophy & theory of education; Educational strategies & policy; Education and state